The importance of circadian rhythms on drug response in hypertension and coronary heart disease - from mice and man - Lemmer, Björn (Pharmacology & therapeutics, 2006)
The cardiovascular system is highly organised in time; blood pressure (BP), heart rate (HR), peripheral resistance, pressure and the release/activity of vasodilating hormones all display pronounced circadian variations. Pathophysiological events within the cardiovascular system are also not random, as shown for instance by sudden cardiac death (SCD), stroke, ventricular arrhythmias (VA), arterial embolism, and symptoms of coronary heart disease (CHD) such as myocardial infarction (MI) and ischemia, angina attacks (AA) in stable angina (stA) or variant angina (varA) or silent ischemia. In hypertensive patients various anti-hypertensive drugs were investigated in crossover studies (morning vs. evening dosing); however consistent data were only obtained for angiotensin-converting enzyme (ACE) inhibitors and calcium channel blockers. Whereas in dippers ACE inhibitors had a super-dipping effect when dosed at night, no consistent difference in BP lowering effect on the 24-hr BP profile was found with calcium channel blockers after morning and evening dosing. In non-dippers the calcium channel blockers isradipine and amlodipine consistently transformed non-dippers into dippers, after evening dosing. Diuretics are also able to normalize a non-dipping behaviour. Moreover, a circadian phase-dependency in pharmacokinetics has been demonstrated for various cardiovascular active drugs such as β-blockers, calcium channel blockers, oral nitrates and ACE inhibitors, modified by the pharmaceutical formulation. There is evidence that in hypertensive dippers anti-hypertensive drugs should be given in the early morning, whereas in non-dippers it may be necessary to add an evening dose or even to use a single evening dose in order to not only reduce high BP but also to normalize a disturbed non-dipping 24 hr BP profile. In CHD, calcium channel blockers-mainly short acting and non-retarded preparations-seem to be less effective than β-adrenoceptor antagonists in reducing ischemic events during the night and early morning. However, the role of formulation and/or subclasses of the calcium channel blockers remains to be elucidated. In order to get more insight into the circadian regulation of the cardiovascular system animal models of primary and secondary hypertension have been studied in various strains of normotensive and hypertensive rats and mice. At least in rodents there is ample evidence that the 24-hr rhythms in BP and HR are under the control of biological clock(s) as they persist under constant darkness (i.e. in free-run conditions) with a period deviating from 24 hr; these rhythms are abolished by lesioning of the “master clock” located in the suprachiasmatic nulcei (SCN). In conclusion, chronobiological and chronopharmacological studies are important experimental and clinical approaches to get a better insight into the physiological and pathophysiologal regulation of the cardiovascular system including their rhythmic organisation. Circadian time-dependent clinical studies also have implications for drug therapy in hypertension and CHD.